2021
DOI: 10.1007/s40615-021-01115-3
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempts Among Racial and Ethnic Groups in a Nationally Representative Sample

Abstract: Objective Evaluate suicide attempt prevalence and potentially related sociodemographic and psychiatric factors among racial and ethnic groups. Methods Between 2012 and 2013, the National Epidemiologic Survey on Alcohol and Related Conditions-III (NESARC-III) conducted semi-structured interviews with 36,309 adults in the USA. We identified lifetime suicide attempt prevalence and significant predictors for each racial/ethnic group using stratified logistic regressions. Analyses were exploratory without a priori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…In addition, the study period coincides with the COVID-19 pandemic, with studies showing a reduction in emergency department visits for suicide attempts (24-26). The study found that younger females had the highest incidence of emergency department visits for attempted suicide, consistent with other studies (8,(27)(28)(29). In contrast to Ivey-Stephenson et al ( 30), this study found the highest incidence of emergency department visits for attempted suicides among patients with private insurance.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the study period coincides with the COVID-19 pandemic, with studies showing a reduction in emergency department visits for suicide attempts (24-26). The study found that younger females had the highest incidence of emergency department visits for attempted suicide, consistent with other studies (8,(27)(28)(29). In contrast to Ivey-Stephenson et al ( 30), this study found the highest incidence of emergency department visits for attempted suicides among patients with private insurance.…”
Section: Discussionsupporting
confidence: 91%
“…[ 5 ] In addition to diagnosed mental illnesses, adverse childhood experiences, feelings of hopelessness, and diathesis (the tendency to experience suicidal ideation and act on suicidal feelings) are also associated with suicidal behavior. [ 4 ] Furthermore, inequalities across countries, [ 6 ] regions, [ 7 ] and ethnicities [ 8 ] have also been identified as contributors to suicide mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Racial and ethnic disparities exist in concussion knowledge, 4 care-seeking, 5 reporting, 4 , 6 and management, 7 and racial and ethnic disparities in mental health awareness, incidence of depression, and treatment are well known. 8 , 9 , 10 , 11 Sex also plays a moderating role in concussion, depression, and suicide attempts, as female adolescents attempt suicide at significantly higher rates than males while males experience concussion at higher rates than females. 12 , 13 , 14 , 15 It is difficult to estimate the rate at which concussions and/or suicide attempts occur for each race and ethnicity because of sample-size limitations of previous studies, differences among racial and ethnic groups in reporting behaviors, and discrepancies in the diagnosis of concussion among races and ethnicities.…”
Section: Introductionmentioning
confidence: 99%